Optimizing daylily (Hemerocallis citrina Baroni) cultivation: integrating physiological modeling and planting patterns for enhanced yield and resource efficiency - Li, Weijia; Zhang, Kun; Liu, Jianxia; Wu, Juan; Zhang, Yue; Henke, Michael (Frontiers in Plant Science, 2024)
Understanding and optimizing the dynamics of plant growth under different planting patterns is essential for effective production of daylilies (Hemerocallis). Optimizing the dynamics of daylily (Hemerocallis citrina Baroni) growth under various planting patterns is critical for enhancing production efficiency. This study presents In this study, we developed a comprehensive model to simulate daylily growth and optimize planting patterns to maximize bud yield while minimizing land resource utilization. The model incorporates the source-sink relationship specific to daylilies into physiological process modeling, considering accounting for environmental factors such as microlight and temperature climate, and CO2 concentration. Furthermore, Sspatial factors, including planting pattern, row spacing, plant spacing, and plant density were integrated to examined for their impact on light interception, photosynthesis, and resource efficiency. Employing partial least square path modeling (PLS-PM), we analyzed the interrelations and causal relationships between planting configurations and physiological traits of daylily canopy leaves and buds.Through in situ simulations,of 36 planting scenarios, we identified an optimal configuration (Scenario ID5)were evaluated, leading to the identification of an optimal planting configuration for daylily cultivation, represented by Scenario ID5, with a density of 83,000 plants•ha -1 , row spacing of 0.8 m, and equidistant planting with a plant spacing of 0.15 m. Employing partial least square path modeling (PLS-PM), we analyzed the interrelations and causal relationships between the plant configuration characteristics of all simulated scenarios and the physiological traits of daylily canopy leaves and buds. Our research findings indicate that an increased in Wide+Narrow row spacing can lead to a corresponding increase in enhance yield to a certain extent. WhileAlthough planting patterns do affect influence daylily yield, their influence overall impact is relatively minor, and there is no clear pattern regarding the impact of plant spacing on individual plant yield. In summary, our This modeling approach provides offers valuable insights into the dynamics of daylily plant growth dynamics and the optimization of planting patterns optimization, providingoffering practical guidance for both farmers and policymakers to enhance daylily productivity while minimizing land use.